Consumer Perception On Oil Commodity: Brand Image Of Shell - Migin, Melissa Wendy (2007)
This paper is an exploratory study focused on Shells brand in the oil commodity market in Malaysia, more specifically in the states of Kuala Lumpur and Selangor. It presents empirical evidence of consumers perception in terms of brand attributes such as brand personality, perceived value with brand image. Moreover, this study will investigate the relationship between brand image and brand loyalty.